Characterization of the bispecific VHH antibody tarperprumig (ALXN1820) specific for properdin and designed for low-volume administration - Paul Tamburini; Dennis Vestergaard Pedersen; Denise Devore; Josh Cone; Rekha Patel; Todd Hunter; Fang Sun; Gregers Rom Andersen; Jeffrey Hunter (Taylor & Francis Group, 2024)
The bispecific antibody tarperprumig (ALXN1820) was developed as a treatment option for diseases involving dysregulated complement alternative pathway (AP) activity that could be administered in small volumes, either subcutaneously or intravenously. Tarperprumig incorporates a C-terminal variable domain of a heavy chain only antibody (VHH) that binds properdin (FP) connected via a flexible linker to an N-terminal VHH that binds human serum albumin (HSA). The purified bispecific VHH antibody exhibits an experimental molecular weight average of 27.4 kDa and can be formulated at > 100 mg/mL. Tarperprumig binds tightly to FP and HSA with sub-nanomolar affinity at pH 7.4 and can associate simultaneously with FP and HSA to form a ternary complex. Tarperprumig potently and dose-dependently inhibits to completion in vitro AP-dependent complement C5b-9 formation, AP-dependent hemolysis, and the AP deposition of C3, FP and C9. X-ray crystallography revealed that the isolated FP-binding VHH recognizes the thrombospondin repeat 5 domain of FP, thereby preventing FP from binding to the AP convertase owing to severe steric hindrance. Tarperprumig cross-reacts with cynomolgus monkey FP and serum albumin. In summary, tarperprumig exhibits properties tailored for subcutaneous administration and is currently in clinical development for the treatment of complement AP-related disorders.